The significance of food blogs in influencing consumers' dining habits in the consumer-centric era - Chang, Ting Hui (2009)
This study explores the importance of food blogs in influencing consumers’ dining habits in the revolutionary Web age, wherein an unprecedented amount of user-generated content is empowering ordinary consumers to become more knowledgeable about like-minded consumers’ consumption experiences. The author focuses on the discussion and shared experiences of observed bloggers and readers’ restaurant visits by applying the essence of netnography, which is an inventive and experiential approach to investigating the tastes, desires, and consumption patterns of postmodern consumers online. The results of this study demonstrate that personal food blogs are virtual tribes in which food lovers accumulate and enhance their knowledge of skilled consumption in the foodservice market. More insightfully, they are inexpensive means of gathering rich, authentic, and unsolicited customer evaluations and capturing consumers’ subtle preferences about their experienced foodservices, therefore enlightening foodservice organisations to ameliorate the overall service quality and to dramatise an extraordinary foodservice performance for customers to savour with obvious relish.